Informality sectoral selection and earnings in Uruguay - Bucheli, Marisa; Ceni, Rodrigo (Estudios Económicos de El Colegio de México, 2010)
In this paper we define an informal worker as one who is not contributing to the social security system. We analyze the likelihood of being an informal worker, and we estimate the differentials in earnings between sectors using the OLS estimation and a switching regression model. We find that formality is more likely among the better-educated, and among men, those residing in the capital city, and heads of households. In addition, we find that according to five different proxies of the average gap for salaried workers and several sub-samples, earnings are higher in the formal than in the informal sector for all the samples.